Pelatihan Bisnis dan Marketing Digital Berbasis Aplikasi WhatsApp Business di SMA Sang Timur Yogyakarta - Ginanjar Setyo Nugroho; Murniady Muchran; Gulam Hazmin; Adi Prasetyo (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This service aims to increase students' knowledge and skills in operating WhatsApp Business as one of the most useful applications to be used as a business and digital marketing tool. Training and mentoring were used in this service. Sang Timur Yogyakarta High School was the service's partner. The evaluation instrument for this activity was interviews, which were analyzed descriptively. The results of this service showed that students had an understanding and skills in using WhatsApp Business, how to sell online correctly, and how to trade and reply to a good chat on WhatsApp Business. Moreover, the service indicated that they understood how to use WhatsApp Business and knew the benefits and advantages of selling online. They also could learn how to do business through WhatsApp Business and understand how to do business better and more accessible. The results were achieved in implementing mentoring, where several participants installed WhatsApp Business for businesses that matched their interests.